Characterization of Cu2O and Cu2O–Ag2O thin films synthesized by plasma oxidation. (August 2015) - Wu, W.; Tseng, C.C.; Li, C.; Chang, C.K.; Hsieh, J.H.
Abstract: Cu2 O and Cu2 O–Ag2 O thin films were synthesized by a plasma oxidation process on uncoated as well as Cu and Cu–Ag(4 at.%) thin-film coated Cu sheets, using an inductively coupled plasma system equipped with four internal antennas. During oxidation, a plasma probe and an optical emission spectrometer were used to characterize the plasma with the variation of O2 /(Ar + O2 ) flow ratios. After oxidation, the structural phases and the growth rate of the oxidized layer were first examined. To compare the photo-electrical properties of Cu2 O and Cu2 O–Ag2 O, the incident-photon-conversion-efficiency of the samples was measured. The results shows that the oxidation rate was increased with the increase of oxygen radicals (O*), which is attributed to the increase of plasma density. Deposited in low oxygen ratio, the oxidized films would have high deposition rate but with more complex structure. The coupling of Ag2 O phase into Cu2 O can enhance light absorption and create more electron–hole pairs due to the narrower band-gap structure of Ag2 O. The effect of Ag2 O phase on the enhanced photocurrent is discussed. Highlights: Plasma oxidation rate and structure of Cu2 O are related to O*/Ar* in plasma. Highest O*/Ar* occurs when oxygen flow ratio is low and the plasma density is high. Cu2 O–Ag2 O composite films are produced using plasma oxidation. Coupling of Ag2 O phase into Cu2 O would contribute to the increase of photo-current.